Amino Acid and Fatty Acid Metabolism Disorders Trigger Oxidative Stress and Inflammatory Response in Excessive Dietary Valine-Induced NAFLD of Laying Hens - Jian, Huafeng; Xu, Qianqian; Wang, Xiaoming; Liu, Yating; Miao, Sasa; Li, Yan; Mou, Tianming; Dong, Xinyang; Zou, Xiaoting (Frontiers in Nutrition, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a chronic and metabolic liver disease and commonly occurs in humans with obesity and type 2 diabetes mellitus (T2DM) and animals including rodents and laying hens. Altered circulating amino acids, in particular, elevated branched-chain amino acids (BCAAs) and aromatic amino acids (AAAs), are consistently reported in patients with NAFLD and T2DM. How long-term dietary individual BCAA such as valine impact amino acid and fatty acid metabolism remains unknown. Here, we demonstrate that when laying hens are fed with dietary valine at the following different levels in a feeding trial that lasted 8 weeks: 0.59, 0.64, 0.69, 0.74, and 0.79%, respectively, long-term exposure to excessive valine diets such as 0.74% and 0.79% dietary valine leads to amino acid imbalance, impaired amino acid metabolism, increased fatty acid synthesis and inhibited fatty acid utilization. Long-term intake excessive dietary valine impaired amino acid metabolism via inhibiting C/EBP-β/Asns mediated by downregulating GCN2-eIF2α-ATF4 pathway and elevating circulating BCAAs and AAAs levels, and ultimately result in amino acid imbalance. High levels of dietary valine stimulating lipid deposition by suppressing GCN2-eIF2α-ATF4-FGF19-TORC1 signaling pathway to promote fatty acid synthesis and repress fatty acid utilization, and eventually accelerate the development of NAFLD. Spearman correlation analysis revealed circulating amino acid imbalance are significantly associated with fatty acid metabolism and enhanced oxidative stress. The inhibition of GCN2-TORC1 pathway induced autophagy suppression to trigger liver oxidative stress and inflammatory response. In conclusion, our results reveal the adverse metabolic response to excessive dietary valine mediated by amino acid and fatty acid metabolism disorder and suggest reducing dietary valine as a novel approach to preventing and treating NAFLD in humans and fatty liver hemorrhagic syndrome (FLHS) in laying hens.